Post-thermal performance of concrete containing clamshell - Ahim, Athirah Izazi; Zuhan, Nurizaty; Saleh, Norharyati; Mohamad, Mazlina; Kado, Bishir (Faculty of Civil Engineering, 2025)
This study investigates the post-thermal mechanical performance of concrete incorporating clamshell powder (CSP) as a partial cement replacement at 0%, 4%, 6%, and 8% by weight. Grade M20 concrete specimens were tested for workability, rebound hardness, compressive strength, and splitting tensile strength at ambient temperature and after exposure to elevated temperatures of 150 °C, 300 °C, and 400 °C. Results showed that workability decreased progressively with higher CSP content due to increased water absorption and coarser particle texture. At ambient conditions, the highest compressive strength (40.35 MPa) was recorded for 8% CSP, an 51.63% improvement over the control mix. Thermal exposure up to 300 °C enhanced compressive strength by approximately 12.2%, attributed to matrix densification and improved bonding, while exposure to 400 °C caused a slight reduction (3.93%) due to microcracking and C–S–H decomposition. Splitting tensile strength peaked at 6% CSP and 300 °C (2.86 MPa), 75.5% higher than the control specimen CS0 (1.63MPa) at the same temperature. A strong positive correlation (R² = 0.72) was observed between compressive and tensile strengths. The findings demonstrate that optimal CSP incorporation (6–8%) can improve both compressive and tensile performance after moderate heat exposure, offering a sustainable and thermally resilient alternative to conventional cement in structural applications.